Fatigue and Sleep Among Employees With Prospective Increase in Work Time Control: A 1-Year Observational Study With Objective Assessment. Issue 11 (November 2016) - Kubo, Tomohide; Takahashi, Masaya; Liu, Xinxin; Ikeda, Hiroki; Togo, Fumiharu; Shimazu, Akihito; Tanaka, Katsutoshi; Kamata, Naoki; Kubo, Yoshiko; Uesugi, Junko
Abstract : Objectives: This observational study aimed to determine how 1-year changes in work time control (WTC) have an impact upon objectively measured fatigue and sleep among employees. Methods: Thirty-nine employees were divided into two groups according to whether or not their WTC increased from baseline to 1 year later. Psychomotor vigilance task (PVT) and wrist actigraphy were used to objectively measure fatigue and sleep, respectively. Self-reported outcomes were also measured. Results: The increased WTC group showed gradual improvements in PVT performance and sleep quality over the course of the follow-up period compared with the not-increased WTC group. Between-group differences were statistically significant for PVT lapses and tended to be significant for PVT speed after 1 year. Conclusions: A progressive increase in WTC could play a crucial role in reducing fatigue and promoting sleep among employees.